2005
DOI: 10.3748/wjg.v11.i12.1798
|View full text |Cite
|
Sign up to set email alerts
|

Four-year follow up of hepatitis C patients vaccinated against hepatitis B virus

Abstract: AIM:Patients with chronic hepatitis C have been recommended to receive vaccinations against hepatitis B. Our study aimed at evaluating the hepatitis B immunogenicity and efficacy against hepatitis B virus infection 4 years after primary immunization series in a group of patients with chronic hepatitis C. METHODS:We recruited 36 out of 48 hepatitis C virus (HCV) infected individuals who were vaccinated against hepatitis B virus (20 g of recombinant HBsAg at 0-1-6 mo schedule) in 1998. Here we measured anti-HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The overall seroconversion rates 1 month after a single booster dose were 80% in patients and 96% in controls, which is compatible with studies reporting reduced vaccine immunogenicity in patients with CHC compared with healthy individuals. 9,10,12 As in previous reports including adults, 6,7,9,12 no correlation was observed between antibody response and age, gender, body mass index, baseline ALT levels, HCV viral load and stage and grade of liver disease. The anti-HBs seroconversion rates were different between those who responded to treatment with interferon-a and ribavirin administered after primary hepatitis B vaccination and those who did not (P50.02).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The overall seroconversion rates 1 month after a single booster dose were 80% in patients and 96% in controls, which is compatible with studies reporting reduced vaccine immunogenicity in patients with CHC compared with healthy individuals. 9,10,12 As in previous reports including adults, 6,7,9,12 no correlation was observed between antibody response and age, gender, body mass index, baseline ALT levels, HCV viral load and stage and grade of liver disease. The anti-HBs seroconversion rates were different between those who responded to treatment with interferon-a and ribavirin administered after primary hepatitis B vaccination and those who did not (P50.02).…”
Section: Discussionmentioning
confidence: 48%
“…4 In patients with CHC, the immunogenicity of the HBV vaccine has been investigated in several studies including adults, and in some the response to the vaccine is reduced. [5][6][7][8][9][10][11][12] This study reports the rate of response to the HAV and HBV vaccines, duration of protection and the incidence of acute HAV or HBV infections during follow-up in patients with CHC compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HCV-positive patients, however, appear to have a decreased responsiveness to the HAV or HBV vaccines [92][93][94][95], and Leroy et al [96] demonstrated that HCV viraemia levels were inversely correlated with titres of anti-HBs developing after vaccination. HCV infection impedes dendritic cell maturation and T-cell proliferation [97][98][99], and the dysfunction of these cells impairs Blymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…A Poland study reported more than 60% CHC patients lost protective anti-HBs four years after HepB immunization and anti-HBs level at follow-up were much lower among CHC patients compared with healthy control (18.3 mIU/mL vs 156.0 mIU/mL), which was in line with the present study. 17 …”
Section: Discussionmentioning
confidence: 99%